Manajemen Penyiaran Radio DCS FM Dalam Mempertahankan Program Classic Oldies di Kalangan Pecinta Musik di Madiun - Fadil Wisda Rahman; Sanhari Prawiradiredja (ETTISAL : Journal of Communication, 2017)
AbstrakThe research entitled "Radio Broadcast Management DCS FM in Maintaining Classic Oldies Program among Music Lovers in Madiun". The purpose of this research Is to know how the management of DCS FM radio in managing Classic Oldies program so that still can exist until now. Data processing techniques that researchers use is by field observation, interviews, and literature study. In the management of its radio show program, DCS FM Madiun radio keeps up with the times and technological developments to merge with its market. The market in question here is the DCS FM Madiun radio listeners who are mostly young people. DCS FM Radio really follow the willingness of the audience, because Classic Oldies program is also as a medium of communication for its loyal listeners. Communication media is meant to share experiences, knowledge of music or musicians ranging from fashion, lifestyle, and the latest info from their idol musicians. AbstractThe researchentitled "Radio BroadcastManagement DCS FM in MaintainingClassicOldies Program among Music Lovers in Madiun". The purposeofthisresearchistoknowhowthemanagementof DCS FM radio in managingClassicOldies program sothatstillcanexist until now. Data processingtechniquesthatresearchersuseisbyfieldobservation, interviews, andliterature study. In themanagementofits radio show program, DCS FM Madiun radio keepsupwiththetimesandtechnologicaldevelopmentstomergewithitsmarket. The market in questionhereisthe DCS FM Madiun radio listenerswho are mostlyyoungpeople. DCS FM Radio reallyfollowthewillingnessoftheaudience, becauseClassicOldies program isalso as a medium ofcommunicationforits loyal listeners. Communication media ismeanttoshareexperiences, knowledgeof music ormusiciansrangingfromfashion, lifestyle, andthelatest info fromtheiridolmusicians.